Water treatment gives back to grid. Issue 3 (May 2020) - Unknown
Abstract : Hidden away in a remote part of East Lothian in Scotland is one of Scottish Water's most environmentally friendly sites. The Castle Moffat Water Treatment Works uses water from the Whiteadder reservoir and is generating more energy than it uses.